META-MODELE D’INTEGRATION DE LA MAINTENANCE EN CONCEPTION - Nzie, Wolfgang; Kenmeugne, Bienvenu; Garro, Olivier (European Scientific Journal, ESJ, 2014)
The emergence of any product during design is gradual thanks to the different professionals who generally input their diverse views and opinions. This is considered in the Distributed Design Model, where these professionals are not only networkly connected, but have their own languages, tools and methods for data communication. The framework FBS (Function-Behavior-Structure), earlier considered allows the object of maintenance to be modelled in three ways: functional model of maintenance, structural model of maintenance and behavioural model of maintenance. Based on the Distributed Design Approach, the algebraic formulations of maintenance languages have been described to model maintenance integration. In this work, we first propose a meta-model of maintenance that captures all points of specific views of the maintenance professionals on the design object and gives a holistic view of maintenance during design process. Next, design methods and tools are identified to facilitate the utilization of the meta-model during design process, maintenance, dismantlement and recycle of product. Lastly the statement of an optimization maintenance problem is highlighted.The effort has been made for the given mathematical function to establish the results by using Lagrangean multiplier method. The validation of the meta-model should be an illustrative prespective in the real concurrent design process.